2006
DOI: 10.21236/ada443252
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Components for High-g Hardened Packaging

Abstract: Approved for public release; distribution is unlimited.ii REPORT DOCUMENTATION PAGE Form Approved OMB No. 0704-0188Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection information. Send comments regarding this burden estimate or any other aspect of this collection of information, including sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…During each phase, these electronics are expected to retain full functionality. In an effort to mitigate the severity of these loads, electronic components are oen potted to enhance structural support, dampen large dynamic vibrations due to gun launch [1]. Electronic components are also potted in order to protect sensitive equipment from environmental conditions (such as moisture), as well as to insulate electrical leads in the event that other components fail [2].…”
Section: Introductionmentioning
confidence: 99%
“…During each phase, these electronics are expected to retain full functionality. In an effort to mitigate the severity of these loads, electronic components are oen potted to enhance structural support, dampen large dynamic vibrations due to gun launch [1]. Electronic components are also potted in order to protect sensitive equipment from environmental conditions (such as moisture), as well as to insulate electrical leads in the event that other components fail [2].…”
Section: Introductionmentioning
confidence: 99%
“…with each other during deformation has not been explicitly tested. Based on the preliminary physical hardware testing, it was shown that the TT-3 robot was not damaged by rod collision, but more elaborate analyses and experiments should be performed in order to guarantee the robustness of the robot under high g-forces [19]. In the future, impact tests with systematically changing physical parameters (e.g., pretension) to characterize the behavior of the robot under different impact conditions will be performed.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%